1999
DOI: 10.1016/s0040-4039(99)00696-6
|View full text |Cite
|
Sign up to set email alerts
|

The first example of an intramolecular Westphal reaction. Synthesis of a new aza-quinolizinium type system

Abstract: The first example of an intramolecular Westphal condensation is described. To test the utility of this reaction, new benz(l)azino[2,1-a]phthalazinium salts have been prepared from appropriate dicarbonyl precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[17][18][19][20][21][22] The search in our lab for new azaquinolizinium-type cations having the requisites previously established for intercalation led us to focus on different possibilities for incorporating the azaquinolizinium moiety into a nonlinearly fused tetracyclic cation. The retrosynthetic analysis of one of the desired systems (Scheme 2) indicated that the intramolecular Westphal reaction 23 could be the choice for a straightforward synthesis of benzo [f]pyrido[2,1-a]phthalazinium cations 3 from the salt 10, which was envisioned to originate from the alkene 8. Thus, our approach was to use isocromane 5 as the key raw material, convert it to a 2-haloethyl benzaldehyde 6, and prepare 8 through a Wittig reaction.…”
Section: Chemistrymentioning
confidence: 99%
“…[17][18][19][20][21][22] The search in our lab for new azaquinolizinium-type cations having the requisites previously established for intercalation led us to focus on different possibilities for incorporating the azaquinolizinium moiety into a nonlinearly fused tetracyclic cation. The retrosynthetic analysis of one of the desired systems (Scheme 2) indicated that the intramolecular Westphal reaction 23 could be the choice for a straightforward synthesis of benzo [f]pyrido[2,1-a]phthalazinium cations 3 from the salt 10, which was envisioned to originate from the alkene 8. Thus, our approach was to use isocromane 5 as the key raw material, convert it to a 2-haloethyl benzaldehyde 6, and prepare 8 through a Wittig reaction.…”
Section: Chemistrymentioning
confidence: 99%
“…375 When treated with Br 2 under light-irradiation, isochromenones are regioselectively halogenated adjacent to oxygen (Scheme 251). 376 The resulting species are prone to ringopening, which can be performed by adsorption on silica gel and subjection to microwave irradiation, affording 2-(2-bromoethyl)benzaldehyde 950a in good yield. Analogously, brominated benzophenones 950b-e were synthesized in reasonable to excellent yields from 1-phenylisochromanes 949b-e. 234…”
Section: Radical Halogenationsmentioning
confidence: 99%